Getting Smarter About Mitigating Energy Losses - Fichen, Yvon (T.C. Bilim, Sanayi ve Teknoloji Bakanlığı, 2014)
Energy loss is a real issue that can have significant financial and environmental impacts for utilities and their customers. It is easier and more costeffective to directly tackle the problem of losses rather than investing in new production methods. According to the World Bank, it is three times cheaper to save 1 kWh of electricity by improving the efficiency of the distribution network than investing in a new way of producing this kWh. In addition, the World Energy Council identifies nontechnical losses and high non-recovery rates as one of the most important factors contributing to financial losses. In Turkey, utilities are also facing these types of challenges and have put in place actions in order to address these concerns. Nevertheless, there is still more to be done. Investment in smart metering solutions can help address the issue of both technical and nontechnical losses. For instance, smart metering solutions can help: Locate and analyse energy losses on the network Analyse and optimise network infrastructure Detect tampering conditions Ensure proper billing Identify consumption anomalies and discrepancies This paper will highlight new ways to address energy losses, such as energy diversion detection and energy balance assessment. It will also demonstrate how utilities can experience significant cost-savings. It will detail specific examples of their energy losses in action and discuss how to identify and remediate operational problems based on Itron’s insight and experience, combined with our smart metering solutions and consulting services.